EFFECT OF MIXED BIO-FERTILIZERS AND NITROGEN LEVELS ON GROWTH, YIELD ATTRIBUTES AND YIELD OF PEARLMILLET - Rathod, B.S.; Singh, V.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted at Research farm of CCS Haryana Agricultural University, Hisar during kharif 2002. Nine treatments viz., control, seed inoculation with mixed bio-fertilizers, 50 RDN, 75% RDN, 100% RDN, 125% RDN, 50% RDN + mixed biofertilizers, 75% RDN + mixed bio-fertilizers and 100% RDN + mixed bio-fertilizers were tested in randomized block design with four replications.Application of 125% RD resulted in significantly higher grain and stover yield except 100% RDN, 75% RDN+mixed bio-fertilizer and 100% RDN+mixed bio-fertilizer. However,stover yield in 75% RDN+mixed bio-fertilizer significantly increased the grain and stover yieldover control